Analysis of the constraints to the realization of the aims of the language in-Education policy of South Africa - Chitapi, Itai (My University, 2018)
The South African Language in Education Policy (LiEP) of 1997 was created to contribute to the transformation of the education sector and of South Africa as a whole, through its promotion of the recognition and use of African languages that were marginalised during the apartheid era. The mechanism of additive bilingualism was identified as the key to achieving the goals of quality education and equitable treatment within a pragmatic framework. However, two decades on, LiEP has not been effectively implemented, nor does its implementation appear imminent. Spolsky’s (2004) framework posits that language policy functions at three levels: ideology, management and practice. Applying this framework, and using a combination of novel documentary analysis of the LiEP itself and eight in-depth expert interviews, this study examines the constraints that have limited implementation of the LiEP. The constraints within the LiEP policy text itself include the ideological separation of education from Black Economic Empowerment; and the policy management decisions within the Department of Basic Education (DBE) to ignore curriculum planning, and to postpone the completion of the LiEP document and regulations. The constraints arising out of the “public” expression of language policy within and beyond the education sector occur at all three levels. At ideological level, constraints include the lack of a unified ideological position within the DBE, and the side-lining of the LiEP by the DBE. At management level, public attitudes against the extended use of African languages are a critical constraint. Inadequate resourcing of the ‘multilingual project’, in terms of teacher and materials development, is a further constraint limiting LiEP implementation. At practice levels, the ongoing hegemony of English and the related collusive practice of elite closure continue to thwart LiEP implementation. The completion of the LiEP, its integration into the DBE’s main programmes and its overt promotion within and beyond education are the key recommendations. These policy management steps should be aligned explicitly and directly with economic empowerment initiatives and imperatives.
Research Report Submitted in partial fulfillment of the requirements for the degree of Master of Management in Public Policy
Keywords: Language policy--South Africa; Curriculum planning--South Africa; Multilingualism--South Africa; Language and education--South Africa